IMPLEMENTING RECONSTRUCTIONISM PHILOSOPHY IN LEARNING ENGLISH: A CASE STUDY FOR 5TH GRADE STUDENTS IN PRIMARY SCHOOL - Nuraini, Hery; Hasani, Aceng; Nulhakim, Lukman (JPSD (Jurnal Pendidikan Sekolah Dasar), 2024)
Reconstructionism is a philosophical school that emphasizes change and renewal of the education system. Technological advances influence changes and developments in the education system. English as a second language for students in Indonesia brings challenges in the learning process, as felt by students in 5th grade at SDN Kedaung Wetan 3 who consider English very difficult to learn due to their lack of vocabulary knowledge. The presence of technology as a media is expected to solve the problems the students face. This research aims to describe the implementation of the reconstructionism philosophy in learning English. This research uses a qualitative method using observation, interview, and documentation as research instruments. The subjects of this research are three students from 5th grade and one English teacher, with 4 respondents as the subject research. The observation, interview, and test results show that changes in the education system apply culture to forming student’s character through the Adiwiyata program. Apart from that, this school also experienced changes in the curriculum’s implementation from using the 2013 Curriculum to Kurikulum Merdeka following central government policy. Changes have also occurred in learning English, where teachers and students use textbooks and media such as the Quizizz application and YouTube to deliver the material. It also shows positive findings in achieving their vocabulary.